1994
DOI: 10.1007/bf00022526
|View full text |Cite
|
Sign up to set email alerts
|

Control of ripening in transgenic tomatoes

Abstract: Major progress has been made over the last few years in the identification and regulation of tomato ripening genes . At least 25 genes showing elevated expression during ripening have been cloned and several, including polygalacturonase, which modifies fruit textures, have been shown to be ripening-specific . In addition, genes have been cloned for ACC synthase and ACC oxidase, which control the synthesis of ethylene, which plays a critical role in ripening . Inhibition of expression of polygalacturonase, pect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…From this, it can be concluded that the procedure effectively selects for sequences that are uniquely present in green or red tomatoes, or that the two physiological conditions have very little in common. The latter may be true, since the green/breaker stages are reported to be the physiologically most active stages of ripening (Moore et al, 2002) with declining and markedly changed physiological activity towards the more mature, red stages (Fraser et al, 1995;Kende, 1989;Grierson and and Fray, 1994;Giovannoni et al, 1989). Recent literature suggests (LemaireChamley et al, 2005) it is likely that the physiological activity in the developing green fruit is even higher, but this is outside the scope of the experiments discussed here.…”
Section: Discussionmentioning
confidence: 67%
“…From this, it can be concluded that the procedure effectively selects for sequences that are uniquely present in green or red tomatoes, or that the two physiological conditions have very little in common. The latter may be true, since the green/breaker stages are reported to be the physiologically most active stages of ripening (Moore et al, 2002) with declining and markedly changed physiological activity towards the more mature, red stages (Fraser et al, 1995;Kende, 1989;Grierson and and Fray, 1994;Giovannoni et al, 1989). Recent literature suggests (LemaireChamley et al, 2005) it is likely that the physiological activity in the developing green fruit is even higher, but this is outside the scope of the experiments discussed here.…”
Section: Discussionmentioning
confidence: 67%
“…vis1 is regulated by fruit ripening and high temperature and exhibits a typical heat shock protein chaperone function when expressed in bacterial cells. We propose that VIS1 contributes to physiochemical properties of juice, including pectin depolymerization, by reducing thermal denaturation of depolymerizing enzymes during daytime elevated temperatures.Ripening of fleshy fruits is a dynamic transitional period that encompasses a myriad of biochemical and physiological changes leading to easily perceivable alterations in fruit texture, firmness, pigmentation, aroma, and sweetness (Tucker, 1993;Grierson and Fray, 1994). Significant progress has been made in characterizing the molecular components of fruitripening process, including ethylene biosynthesis and perception, cell wall depolymerization, light signal transduction, and carotenoid accumulation (Giovannoni, 2001).…”
mentioning
confidence: 99%
“…Ripening of fleshy fruits is a dynamic transitional period that encompasses a myriad of biochemical and physiological changes leading to easily perceivable alterations in fruit texture, firmness, pigmentation, aroma, and sweetness (Tucker, 1993;Grierson and Fray, 1994). Significant progress has been made in characterizing the molecular components of fruitripening process, including ethylene biosynthesis and perception, cell wall depolymerization, light signal transduction, and carotenoid accumulation (Giovannoni, 2001).…”
mentioning
confidence: 99%
“…Several types of transgenic tomato have been produced commercially (see KRIDI. and SHEWMAKER 1996;KRAMER and REDENBAUGH 1994;GRIERSON and FRAY 1994). Another approach to improved flavor is the expression of the sweet protein monellin in both tomato and lettuce (PENARRUBIA et al 1992).…”
Section: Plant Qualitymentioning
confidence: 97%